A telephonic cardiology advice line was effective during the COVID-19 pandemic in both reassuring patients and in ensuring patients received optimal urgent care. (14th October 2021) - Devlin, J; Peace, A J; McGlinchey, P G
Abstract:  : A decrease in patients accessing health care was documented during the first COVID-19 surge. We established a 24/7 cardiology telephone advice service during the first surge, this was provided by an experienced cardiology nurse based in a nurse-led cardiac assessment unit. Various options were available on the basis of the telephone consultation. We particularly wanted to see the outcomes of reassurance of patients (to see if the approach was safe) and the outcomes of patients who were directed to emergency departments (to see if this identified patients with significant cardiological and medical problems who may not otherwise have accessed healthcare). We reviewed the progress of the first 999 patients who used the telephonic service for which we had 90 day follow-up data. 141 patients were initially reassured by the nurse at the telephone call. Of these, 55 patients had no further engagement with healthcare providers in the subsequent 90 days. 7 were followed-up within the cardiac rehabilitation program that they were already participating in. 21 were referred to cardiology by their GP but all subsequently had normal assessment and/or investigation. 30 attended an emergency department of whom 22 were discharged directly from the ED; the other 8 patients were admitted to hospital which included 2 patients with non-cardiac chest pain and 2 with exacerbations of known heart failure. 28 patients recontacted the telephonic service during the 90 days and had subsequent face-to-face assessment. There was one death amongst the 141 patients, from a known malignancy. 161 patients were advised to attend an emergency department following telephonic evaluation of whom 50 did not attend. 84 patients were discharged home following assessment in the emergency department of whom 18 were discussed or referred to cardiology for outpatient assessment. 20 patients were admitted under cardiology (8 non-STEMI, 1 complete heart block, 1 profound bradycardia, 1 atrial fibrillation, 1 congestive cardiac failure, 1 critical aortic stenosis, 1 chemotherapy associated cardiotoxicity, 4 no significant cardiac issue found). Nine patients were admitted to non-cardiac wards. We believe that nurse-led telephonic triage can be effective in the management of patients in the community with established cardiac disease or with potential cardiac symptoms. We intend to further develop the service we established during the first surge of the COIVD-19 pandemic. FUNDunding Acknowledgement: Type of funding sources: None.